Foxg1 Directly Represses Dbx1 to Confine the POA and Subsequently Regulate Ventral Telencephalic Patterning. (4th March 2019) - Du, Ailing; Wu, Xiaojing; Chen, Hanhan; Bai, Qing-Ran; Han, Xiao; Liu, Bin; Zhang, Xiaohu; Ding, Zhaoying; Shen, Qin; Zhao, Chunjie
Abstract: During early development, signaling centers, such as the cortical hem and the preoptic area (POA), are critical for telencephalic patterning. However, the mechanisms underlying the maintenance of signal centers are poorly understood. Here, we report that the transcription factor Foxg1 is required to confine the POA, a resource of Sonic Hedgehog ( Shh) that is pivotal for ventral telencephalic development. Cell-specific deletion of Foxg1 achieved by crossing Foxg1 fl/fl with Dbx1-cre or Nestin-CreER combined with tamoxifen induction results in a dramatic expansion of the POA accompanied by the significantly increased activity of the Shh signaling pathway. Ventral pattern formation was severely impaired. Moreover, we demonstrated that Foxg1 directly represses Dbx1 to restrict the POA. Furthermore, we found that the ventral pallium was expanded, which might also contribute to the observed patterning defects. These findings will improve our understanding of the maintenance of signal centers and help to elucidate the mechanisms underlying ventral telencephalic patterning.